LINGKUNGAN VEGETASI SITUS PERCANDIAN PADANG LAWAS DAN TUMBUHAN BALAKA - Arfian Arfian (Berkala Arkeologi, 2011)
Based on the results of research on the vegetation around Padang Lawas Temples, Padang Lawas Regency, North Sumatera Province, can be known that Padang Lawas Temple sites are located in vegetation environment of lowland tropical rain forest with a high level diversity of plant families, one of those plant families is Euphorbiaceae with one of its species, Phylanthus emlica. L(Balaka). Phylanthus emlica is a type wild plant that grows open spaces in lowland tropical rain forests. Observing its life characteristic and its habitat, then Balaka plant (Phylanthus emlica) in Padang Lawas Temples’ yards was not planted in purpose planted but grows naturally. Balaka plant (Phylanthus emlica) has different name in every area. In Melayu, this plant is known as malaka. In Minangkabau known as balaka, in Sunda known as malaka and in Java, this plant is known as Kemloko, meanwhile in Madura and Bali this plant is called mlakah ,and karsinta in Flores (NTT)